Enhancing the Supercapacitive Behaviour of Cobalt Layered Hydroxides by 3D Structuring and Halide Substitution - Seijas Da Silva, Álvaro (2024)
Among the two-dimensional (2D) materials, layered hydroxides (LHs)stand out due to their chemical versatility, allowing the modulation ofphysicochemical properties on demand. Specifically, LHs based onearth-abundant elements are promising phases as electrodematerials for energy storage and conversion. However, thesematerials exhibit significant drawbacks, such as low conductivity andin-plane packing that limits electrolyte diffusion. In this work, weexplored the synthetic flexibility of α-Co hydroxides (Simonkolleite-likestructures) to overcome these limitations. We elucidated the growthmechanism of 3D flower-like α-Co hydroxyhalides by using in situSAXS experiments combined with thorough physicochemical,structural, and electrochemical characterization. Furthermore, wecompared these findings with the most commonly employed Co-based LHs: β-Co(OH)₂ and CoAl layered double hydroxides. While α-Co LH phases inherently grow as 2D materials, the use of ethanol(EtOH) triggers the formation of 3D arrangements of these layers,which surpass their 2D analogues in capacitive behavior. Additionally,by taking advantage of their anion-dependent bandgap, wedemonstrated that substituting halides from chloride to iodideenhances capacitive behavior by more than 40%. This findingconfirms the role of halides in modulating the electronic properties oflayered hydroxides, as supported by DFT+U calculations. Hence, thiswork provides fundamental insights into the 3D growth of α-Co LH andthe critical influence of morphology and halide substitution on theirelectrochemical performance for energy storage applications.